Knowledge of Ghana’s liberal abortion law and use of modern contraceptives among women of reproductive age - Maxwell Tii Kumbeni; Jeff Luck; S. Marie Harvey (Reproductive Health)
Abstract Background Modern contraceptives have been widely promoted as an effective tool for birth control. They are highly effective for preventing unintended pregnancies thereby reducing the risk of abortions, maternal morbidities, and mortalities. Abortion or planned abstinence from sexual intercourse may be perceived as alternatives to the use of modern contraceptives. The aim of this study was to assess whether knowledge of the legal status of abortion, and knowledge of the monthly fertile period, were associated with the use of modern contraceptives among women of reproductive age in Ghana. Methods We used nationally representative secondary data from the 2017 Ghana Maternal Health Survey. A weighted sample of 23,466 non-pregnant women aged 15–49 years were included in the study. Pearson chi-square and multivariable logistic regression analysis were conducted to assess the association between the independent and the outcomes variables. Sampling weight, cluster, and strata were applied at all levels of the analysis. Results More than half (55.4%) lived in urban area, 80.1% were 20 years or older, 52.2% were multiparous women, 61.9% had secondary or higher education, and 34.5% were in the lower two wealth quintiles. We found no statistically significant association between knowledge of the legal status of abortion and use of modern contraceptives, or between knowledge of the monthly fertile period and use of modern contraceptives. Women with history of an induced abortion were 1.57 times as likely to use modern contraceptives compared to those with no history [adjusted odds ratio (aOR) 1.57, 95% CI 1.41–1.75]. Each additional increase in knowledge of a different modern contraceptive method was associated with 1.25 times increase in modern contraceptive use (aOR 1.25, 95% CI 1.22–1.29). Conclusions Intensifying education on modern contraceptive methods and use, especially at abortion facilities, may help improve the uptake of modern contraceptives among women in Ghana.